Identification and Prioritization of Factors Influencing Afghan Migration Abroad (Salam International Academic Journal, 2025)
Migration has become an increasingly prominent issue in recent decades, gaining significant momentum among the Afghan population. As a major social concern, migration has multiple dimensions that affect various areas of society. Understanding the full scope of migration requires perspectives from more than one academic field. This study aimed to identify and rank the key factors behind the migration of Afghans to other countries. The research was conducted using a sample from Herat province, including local residents and faculty members at Herat University. Data collection involved both semi-structured interviews and a questionnaire. For the qualitative part, participants were selected using purposive sampling. After identifying the main factors behind Afghan migration, the quantitative (field) sample—consisting of 240 residents of Herat—was selected using simple random sampling, based on the Schumacher and Lomax formula. The qualitative data were analyzed through content analysis, while the quantitative data were examined using the Friedman test in SPSS software (version 26). The content analysis of the interviews revealed 32 concepts linked to the drivers of migration. These factors were grouped into six main categories: economic, social, political, cultural, geographical, and educational. To rank these factors, the study matched the findings with the components of a standard migration questionnaire developed by Ronak Nowshin (2013) and Yousef Irani (2011). According to the Friedman test results, economic factors were ranked first, followed by social (2nd), educational (3rd), cultural (4th), geographical (5th), and political factors (6th). This ranking was statistically significant at the 0.000 level with a 95% confidence level.
Keywords: Migration; Economic; Social; Cultural; Political; Geographical; Educational